A Cultural Study of ‘Gular’s Flower’ Novel - Kalpana Luitel (Interdisciplinary Journal of Management and Social Sciences, 2025)
The presented research article focuses on the analysis of the title of the cultural study of the novel ‘Gularko Poomal’ written by novelist Madhav Pyakurel. The necessary material for this article has been collected from library sources. The novel has been studied, and conclusions have been reached through qualitative methods. In this study, the study of the novelistic environment of Gular’s ​​Poomal novel and class study have been conducted. Here, the study of the political environment, economic environment and socio-cultural environment has been conducted under the novelistic study. Similarly, under the class study, class relations, lower class problems, class harmonization approach, presentation of class friendship, economic inequality, indifference towards the higher (exploitative) class ideology, deprivation of service facilities, presentation of lower-class psychology, class basis and characterization of the characters have been studied. Rudal Sahni, Kalautiya, Baje and Harke have been characterizations of the characters. This is a novel written based on the lower-class poor characters living on the border of Nepal and India. All the main characters used in it are marginalized lower classes. It has been concluded that due to the political changes that have taken place in Nepal from time to time, only the system and the people who govern have changed, the trend of governance has remained the same and the situation and problems of the people have been increasing.